Learning and intelligent optimization : 12th International Conference, LION 12, Kalamata, Greece, June 10-15, 2018, Revised selected papers /: 12th International Conference, LION 12, Kalamata, Greece, June 10-15, 2018, Revised selected papers. ([2019]) - Unknown
No abstract available